2016
DOI: 10.1016/j.solener.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Shading-induced failure in thin-film photovoltaic modules: Electrothermal simulation with nonuniformities

Abstract: Finite element electrothermal modeling is employed to study shading-induced failure in monolithically integrated thin-film photovoltaic modules. A key element is spatial nonuniformity in current-voltage characteristics, which causes inhomogeneous current flow when part of a module is under reverse bias due to shading. Time-dependent calculations show that spots with lower reverse breakdown voltage experience greater current density and localized thermal runaway that can cause permanent damage, resulting in ohm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
0
18
0
1
Order By: Relevance
“…The device model designed by Nardone et al demonstrated that reverse-bias breakdown is likely to occur at regions with low reverse-bias breakdown voltage. 6 A significant spike in temperature around sites with reduced breakdown voltages was found under reverse bias, with higher temperatures occurring for encapsulated devices relative to unencapsulated devices. In the present work, we simulate partial shading conditions by applying reverse bias to unencapsulated devices in the laboratory to observe thermal-runaway breakdown events.…”
Section: Andmentioning
confidence: 98%
See 4 more Smart Citations
“…The device model designed by Nardone et al demonstrated that reverse-bias breakdown is likely to occur at regions with low reverse-bias breakdown voltage. 6 A significant spike in temperature around sites with reduced breakdown voltages was found under reverse bias, with higher temperatures occurring for encapsulated devices relative to unencapsulated devices. In the present work, we simulate partial shading conditions by applying reverse bias to unencapsulated devices in the laboratory to observe thermal-runaway breakdown events.…”
Section: Andmentioning
confidence: 98%
“…The rapid localized heating creates a large temperature gradient at which point heat conduction away from the shunt dominates, resulting in cooling of the shunt until stabilization is achieved. Additional discussion on these points can be found in Nardone et al…”
Section: Modeling Thermal‐runaway Reverse‐bias Breakdownmentioning
confidence: 99%
See 3 more Smart Citations